(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper exhibits a review of the primary attributes of cloud computing, where they are uncovered, their principle parts and methods for use. In addition to the technological review that is done, is also carried out. To understand how cloud computing can lead to a powerful ally of SMEs in the context of organizational competitiveness in a world where the role of information systems for a long time proved decisive it is a reflection that the SMEs, whose core business is not technology, need to be carried out.